ANALISIS AKUNTABILITAS PEMERINTAH DESA DALAM MENGELOLA ALOKASI DANA DESA (ADD) PERIODE TAHUN ANGGARAN 2017/2018 - Ridho Agus Mahendra; Indah Listyani; Agung Sulaiman (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
The problem that is the focus of this research is Accountability and Financial Transparency which includes financial integration and reports on the validity and accountability of Karangrejo Village in Ngasem District, Kediri Regency. The data used as observations are the Village Funds Report in Karangrejo Village, and the sample is the Village Fund Allocation report in Karangrejo Village for the period of 2017/2018. The method used in this research is qualitative with interviews and document studies. Based on the analysis conducted, the results of the study are obtained: (1) Village fund program planning has applied the principle of accountable, transparent and participatory where the planning is carried out through the musrenbangdes forum (Village Development Planning Conference). (2) The implementation has implemented the principles of transparency, accountability and participation by involving the community in activities, especially physical development and the community also directly supervises development activities. (3) Accountability in reporting and accountability of village funds is carried out in accordance with the mechanism based on the provisions even though there are still village officials negligence and the activity management team.